“Efecto de cuatro dosis de materia orgánica (pollaza) en el cultivo de ají pimentón (capsicum annuum L.) variedad california wonder, en el distrito de Lamas” - Lozano Sanchez, Mauro (2016)
This research deals with the effect of four doses of organic matter (pollaza) in the cultivation of chili pepper (Capsicum annuum L.) variety California Wonder, in the district of Lamas. We start with the following specific objectives: To assess the implementation of four doses of organic matter (pollaza) in the development and crop yield chili pepper (Capsicum annuum L.) variety California Wonder in the district of Lamas and perform economic analysis far each treatment. To reach the general objective: Determine the application rate of organic matter (pollaza) most suitable far the development and production of the crop chili pepper (Capsicum annuum L.) variety California Wonder in the district of Lamas. The experimental field comprises a dedicated purely to growing vegetables such as cucumber, green onion, pepper, tomato, broccoli area far 25 years. The design of randomized complete block with 5 treatments and 4 replicates per treatment is applied far a total of 20 experimental units. The information processing was performed using the program SPSS 22. Analysis of variance P <0.01 and P <0.05 and Multiple Range Test of Duncan ata P <0.05 was used. The Pollaza used carne from the poultry farm "El Pacifico" located in the district and province of Lamas. She hadan age of two anda half months. The treatments were: control (no pollaza) 1 O, 20, 30 and 40 pollaza tn.ha-1 . he conclusions reached were that the application of 40 t ha-1 pollaza (T 4) as a source of organic matter applied to growing paprika pepper (Capsicum annuum L) variety California Wonder, the highest average yield was obtained with 41120. 7 kg ha-1 and the best agronomic traits in plant height with 44.7 cm, 24.53 flowers per plant, 19.0 fruits per plant, 8.9 cm fruit diameter and 246.7 g of fruit weight. Growing applications pollaza determined positiva linear responses of the variables evaluated and the application 40 tn.ha-1 pollaza the highest value of B I C 0.84 and a net profit of SI was obtained. 11,294.14 soles, resulting in treatment with better profitability. Keywords: Pollaza, organic matter, yield per hectare, profitability